PERENCANAAN DAN PENGEMBANGAN KAMPUNG MADONG SEBAGAI DESTINASI MINAPOLITAN KAMPUNG IKAN BERBASIS MASYARAKAT : ( Kajian Pendekatan Tematik, Holistik, Integratif dan Spasial ) - Amalia, Eva; Pangestoeti, Wahjoe (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
ABSTRACT This research delves into the transformative journey of Kampung Madong, evolving from its current state into a vibrant mina(politan) tourism hub through meticulous spatial planning and regional development. At its core, this development embraces an integrated conservation-based management approach, with a specific emphasis on advancing both fisheries and marine tourism. The overarching goal of the minawisata concept is not only to harness the latent potential of marine resources, fisheries, and tourism but also to foster economic prosperity within the local community. Employing an integrated . thematic , spatial and holistic methodology, the research navigates the comprehensive planning of land use, infrastructure, and resources, with due consideration for their broader societal and environmental implications. Beyond the physical aspects, the study intricately examines cultural and social phenomena, employing thematic and holistic lenses to gain a profound understanding of the dynamics shaping the community. A spatial approach is deployed to map the distribution and interactions within the geographical landscape, envisioning Kampung Madong not merely as a tourist destination but as a community-based fish village, laying the foundation for community-based tourism. In the quest for knowledge, the research utilizes two primary data sources: firsthand accounts gathered through interviews, questionnaires, and direct observations conducted in the field, and secondary data derived from pertinent institutions aligning with the research objectives. The meticulous data collection process unfolds through a methodical field survey, not merely as a strategic guide but as the key to sculpting a sustainable, alluring, and mutually beneficial tourism destination. Despite the multitude of advantages inherent in this approach, the research acknowledges the inherent challenges of coordinating across diverse sectors and comprehending nuanced aspects. Nevertheless, the study underscores the immense potential to elevate positive impacts on the environment, economy, and society, portraying Kampung Madong as a beacon of holistic and sustainable development. Keywords: Approach, Development , Holistic, Integratif, Spacial, Thematic ,